Effect of environmental comfort factors in enclosed transitional space toward work productivity - Kwong, Qi Jie; Adam, Nor Mariah; Tang, Sai Hong (Science Publications, 2009)
Problem statement: The investigated area in this study was the enclosed lift lobby, which distinguishes itself as a unique form of region categorized under building transitional spaces. Such region may act upon on the work performance of occupants, as occupants are sensitive towards the conditions of immediate surroundings. The objective of this study was to investigate the occupants’ perceptions of environmental comfort in the enclosed transitional region with identification of current thermal, visual and acoustic conditions, as well as the effect of the environmental conditions towards work performance. Approach: This survey was performed using both objective and subjective assessments, where comfort related parameters were measured using electronic sensors and the outcomes were analyzed concurrently with results from questionnaire. Results: The results showed that thermal comfort prevails over other two parameters in defining human comfort in the enclosed building area and presumed by most respondents to have more significant impact on work performance. Besides, the environmental factors of the enclosed transitional space exert different level of influences towards work productivity of building occupants. Conclusion: It was necessary to maintain the environmental conditions in the enclosed transitional space, similar to the commonly occupied areas within a building. Further investigation on the individual behavior of occupants in the enclosed region of a building was suggested.